Perspectives on implementing a quality improvement collaborative to improve person-centered care for maternal and reproductive health in Kenya. (15th October 2020) - Giessler, Katie; Seefeld, Avery; Montagu, Dominic; Phillips, Beth; Mwangi, James; Munson, Meghan; Green, Cathy; Opot, James; Golub, Ginger
Absrtact: Objective: To understand perspectives and experiences related to participation in a quality improvement collaborative (QIC) to improve person-centered care (PCC) for maternal health and family planning (FP) in Kenya. Design and setting: Semi-structured qualitative interviews were conducted with members of the QIC in four public health facilities in Kenya. Participants: Clinical and nonclinical public health facility staff who had participated in the QIC were purposively sampled to participate in the semi-structured interviews. Intervention: A QIC was implemented across four public health facilities in Nairobi and Kiambu Counties in Kenya to improve PCC experiences for women seeking maternity or FP services. Main outcome measure: Semi-structured interviews with participants of the QIC to understand perspectives and experiences associated with sensitization to and implementation of PCC behaviors in maternity and FP services. Results: Respondents reported that sensitization to PCC principles resulted in multiple perceived benefits for staff and patients alike, including improved interactions with patients and clients, deeper awareness of patient and client preferences, and improved interpersonal skills and greater job satisfaction. Respondents also highlighted system-level challenges that impeded their ability to consistently provide high-quality PCC to women, namely staff shortages and frequent turnover, high patient volumes and lack of space in their respective health facilities. Conclusion: Respondents were easily able to articulate perceived benefits derived from participation in this QIC, although they were equally able to identify challenges that hindered their ability to consistently provide high-quality PCC to women seeking maternity or FP services.